Transesterification of Castor Oil to Biodiesel by Using Magnesium Oxide as Solid-Base Catalyst - Sylvia, Philip (2013)
All these years fossil fuels are the main resources of energy that meets the world requirements. Gasoline, petrodiesel and natural gas are the fossil-based resources which are limited and insufficient for the future world’s energy demands. Therefore, the search of renewable fuels is a big concern nowadays. Biodiesel is a renewable, environmental friendly and biodegradable fuel that it may substitute conventional fuel with none or very minor engine modification. Environmental issue is one of the concern about the fossil-based fuels because of the emission of total hydrocarbons and carbon monoxide which is contrast with biodiesel due to more complete combustion caused by the increased oxygen content in the flame coming from the biodiesel molecules. Biodiesel is the product from the chemical reaction called transesterification between vegetable oil or animal fat with an alcohol to produce a fatty acid alkyl ester. Methanol is the common alcohol used due to its low cost.Biodiesel can be produced from use waste edible oil or non-edibles oil such as jatropha, castor,and rubber seed. Mostly, the biodiesel today is produced by basecatalyzed transesterification. In this study, the parameters were: methanol to oil ratio of 3:1 and 4:1; and time of 1 hour, 2 hour and 3 hour. For every experiment done, castor oil was heated at 50°C and mixed with methoxide (methanol and Magnesium Oxide) according to the considered parameters. The agitation speed was set at 400 rpm. After the transesterification process completed, the hot mixture was left to settle down for at least one day in a separating funnel. After one day, there were two layers formed. The lower layer of glycerine and catalyst and the upper layer of castor oil methyl ester. The product of castor oil methyl ester was washed with 60°C hot tap water for few times. Next, the product was transferred into a rotary evaporator to remove excess methanol. Then, the product was transferred to a universal bottle and some Magnesium Sulphate was added into it. The mixture was shaken vigorously and was left to settle down for one day. The final product was sucked by using a pipette and then analyzed by using Gas Chromatography-Mass Spectrocopy (GCMS). The highest yield of biodiesel from the research was found to be 78% at methanol to oil ratio of 4:1, reaction time of 3 hours and temperature of 60°C. This study also proved that biodiesel can be produced from castor oil because the GC-MS analysis showed that all the products contained methyl ricinoleate.